Daily potassium intake and sodium-to-potassium ratio in the reduction of blood pressure: a meta-analysis of randomized controlled trials. Issue 8 (August 2015) - Binia, Aristea; Jaeger, Jonathan; Hu, Youyou; Singh, Anurag; Zimmermann, Diane
Abstract : Objective: To evaluate the efficacy of daily potassium intake on decreasing blood pressure in non-medicated normotensive or hypertensive patients, and to determine the relationship between potassium intake, sodium-to-potassium ratio and reduction in blood pressure. Design: Mixed-effect meta-analyses and meta-regression models. Data sources: Medline and the references of previous meta-analyses. Studies eligibility criteria: Randomized controlled trials with potassium supplementation, with blood pressure as the primary outcome, in non-medicated patients. Results: Fifteen randomized controlled trials of potassium supplementation in patients without antihypertensive medication were selected for the meta-analyses (917 patients). Potassium supplementation resulted in reduction of SBP by 4.7 mmHg [95% confidence interval (CI) 2.4–7.0] and DBP by 3.5 mmHg (95% CI 1.3–5.7) in all patients. The effect was found to be greater in hypertensive patients, with a reduction of SBP by 6.8 mmHg (95% CI 4.3–9.3) and DBP by 4.6 mmHg (95% CI 1.8–7.5). Meta-regression analysis showed that both increased daily potassium excretion and decreased sodium-to-potassium ratio were associated with blood pressure reduction ( P  < 0.05). Increased total daily potassium urinary excretion from 60 to 100 mmol/day and decrease of sodium-to-potassium ratio were shown to be necessary to explain the estimated effect. Conclusion: Potassium supplementation is associated with reduction of blood pressure in patients who are not on antihypertensive medication, and the effect is significant in hypertensive patients. The reduction in blood pressure significantly correlates with decreased daily urinary sodium-to-potassium ratio and increased urinary potassium. Patients with elevated blood pressure may benefit from increased potassium intake along with controlled or decreased sodium intake. Abstract : Supplemental Digital Content is available in the text